IDENTIFIKASI KERUSAKAN KAWASAN EKOWISATA HUTAN MERANTI PUTIH (Shorea bracteolata Dyer) DI KABUPATEN KOTABARU - Nor Hamdi; Suyanto Suyanto; Wahyuni Ilham (Jurnal Sylva Scienteae, 2019)
ABSTRACT.This research aim to identify and determine the factors causing damage to ecotourism area of meranti putih forest in Sebelimbingan village and Gunung Sari village, Kotabaru regency, the results of this study are expected to provide benefits and provide input for relevant parties such as local government, the private party to prevent the occurrence of activities that result damaged of the ecotourism forest area meranti putih. In the object of this research is the comunity people who stay in Sebelimbingan Village and Gunung sari Village, the ecotourism forest area meranti putih. The villagers and the survey directly into the forest ecotourism area meranti putih. The results of this research indicate that the people who stay in the around area of ecotourism meranti putih forest do activities that can cause damage to the area. Forest damage is a very important problem faced by all countries in the world. The area of ecotourism forest meranti putih in Kotabaru district have forests damage caused by the community around the forest, the Communitiy people who do cultivation by burn it is one processing efforts form on traditional land, there are rubber plantations as one form of agroforestry activities, pile of rocks illegal mining location conducted by surrounding communities.Keyword: Area damage, ecotourism, meranti putihABSTRAK. Penelitian ini bertujuan untuk mengidentifikasi dan mengetahui factor-faktor penyebab kerusakan kawasan ekowisata hutan meranti putih di desa Sebelimbingan dan desa Gunung Sari kabupaten Kotabaru, hasil penelitian ini diharapkan memberikan manfaat dan memberikan masukan bagi pihak yang terkait seperti pemerintah setempat, pihak swasta untuk mencegah terjadinya kegiatan yang mengakibatkan rusaknya kawasan ekowisata hutan meranti putih.Objek dalam penelitian ini adalah masyarakat yang tinggal di Desa Sebelimbingan dan Desa Gunung sari dan kawasan ekowisata hutan meranti putih, Masyarakat desa tersebut dan survei langsung ke dalam kawasan ekowisata hutan meranti putih. Hasil penelitian ini menunjukan bahwa masyarakat yang tinggal di sekitar kawasan ekowisata hutan meranti putih memang melakukan kegiatan yang dapat menimbulkan kerusakan pada kawasan tersebut.Kata Kunci: Kerusakan kawasan, ekowisata, meranti putih